1976
DOI: 10.1007/bf01537941
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of American Sign Language by a noncommunicating autistic child

Abstract: Experiments in the perception and language abilities of autistic children indicate that the children have auditory-visual association problems. These findings, combined with the findings that autistic communication is primarily gestural, led to the teaching of elements of American Sign Language to a 5-year-old nonverbal autistic boy. Results after 20 hours of training indicate that the child did acquire signs, that increasing signing led to increasing vocal speech, and that the child has rudimentary English sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(38 citation statements)
references
References 15 publications
3
35
0
Order By: Relevance
“…Gardner & Gardner (1969) began training an infant female chimpanzee, named Washoe, to use ASL (American Sign Language) as linguistic communication tool. Some researchers teach sign languages to autistic children who have failed to develop speech and who exhibited poor communication skills and found that sign languages are useful training way for them (Fulwiler & Fouts, 1976;Carr, Binkoff, Kologinsky, & Eddy, 1978;Carr & Kologinsky, 1983). Acredolo & Goodwyn (1985) taught normal infant symbolic gestures and found that despite the heavy use of symbolic gestures, vocal development was advanced.…”
Section: )mentioning
confidence: 99%
“…Gardner & Gardner (1969) began training an infant female chimpanzee, named Washoe, to use ASL (American Sign Language) as linguistic communication tool. Some researchers teach sign languages to autistic children who have failed to develop speech and who exhibited poor communication skills and found that sign languages are useful training way for them (Fulwiler & Fouts, 1976;Carr, Binkoff, Kologinsky, & Eddy, 1978;Carr & Kologinsky, 1983). Acredolo & Goodwyn (1985) taught normal infant symbolic gestures and found that despite the heavy use of symbolic gestures, vocal development was advanced.…”
Section: )mentioning
confidence: 99%
“…If, for example, a slide were labelled by the therapist as "apple" and the attendant identified it as such, an agreement was scored; if a slide were labelled as "apple" and the attendant identified it as "candy" or as "selfstimulation", a disagreement was scored. Like Fulwiler and Fouts, 1976;Smith, 1975). It is often implied that when this method is used, the children will not only learn to discriminate between the various objects on a visual basis but will also learn to discriminate between the spoken words as well (Creedon, 1973;Miller and Miller, 1973;Smith, 1975).…”
mentioning
confidence: 96%
“…A number of clinicians wondered whether other nonverbal organisms, such as autistic children, could also be taught to sign. The initial reports were quite positive in suggesting that sign training could be a viable treatment intervention with such children (Bonvillian and Nelson, 1976; Creedon, Note 1;Fulwiler and Fouts, 1976;Miller and Miller, 1973). However, in the rush of enthusiasm to teach autistic children to use sign language, little attention has been paid to questions of experimental control.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure has been used to successfully target spoken language development in children with autism since the 1970s (Fulwiler & Fouts, 1976;Salvin, Routh, Foster & Lovejoy, 1977). It is also well documented that the use of signs with this population of children has been successful in producing vocal speech when other selection-based communication systems had previously failed (Bonvillian & Nelson, 1976;Carr, 1979;Yoder & Layton, 1988).…”
Section: Sign Language Vs Speechmentioning
confidence: 99%